Exploring the rumen fluid metabolome using liquid chromatography-high-resolution mass spectrometry and Molecular Networking. Issue 1 (December 2018) - Almeida, Rafaela; Prado, Rodolpho; Porto, Carla; Santos, Geraldo; Huws, Sharon; Pilau, Eduardo
Abstract The rumen primary and secondary metabolite content is intimately related to its community of bacteria, protozoa, fungi, archaea and bacteriophages, ingested feed and the host. Despite the myriad of interactions and novel compounds to be discovered, few studies have explored the rumen metabolome. Here, we present the first study using ultra-high performance liquid chromatography tandem mass-spectrometry and Molecular Networking approach, and various extraction methods on the cell-free rumen fluid of a non-lactating Holstein cow. Putative molecules were annotated based on accurate fragmentation matching the Global Natural Products Social Molecular Networking library, public spectral libraries, or annotated manually. The combination of five extraction methods resulted on 1, 882 molecular features observed. Liquid-liquid extraction resulted on the highest molecular features abundance, 1, 166 (61.96% of total). Sixty-seven compounds were annotated using Global Natural Products Social Molecular Networking library and public libraries, such as hydrocinnamic and azelaic acid, and monensin. Only 3.56% of molecular features (67) observed had positive match with available libraries, which shows the potential of the rumen as reservoir of novel compounds. The use of untargeted metabolomics in this study provided a snapshot of the rumen fluid metabolome. The complexity of the rumen will remain long unknown, but the use of new tools should be encouraged to foster advances on the rumen metabolome.